PENERAPAN UNSUR MELAWAN HUKUM DALAM PERKARA TINDAK PIDANA KORUPSI (STUDI KASUS PUTUSAN NOMOR : 74/Pid.Sus-TPK/2021/PN.Bdg) - Regentio Candrika Komala Dewa (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
In the Corruption Court Decision at the Bandung District Court Number 74 / Pid.Sus-TPK / 2021 / PN.Bdg stated that the Defendant was found guilty in the first charge of subsidair, namely Article 3 of the PTPK Law because of the position held by the Defendant as Chairman of the SIPS Cooperative. In formulating its considerations, the panel of judges did not fully include the views of Nur Basuki Minarno. As a result, the panel of judges erred in applying the article. From this, the question arises, how is the concept and regulation of unlawful elements in corruption crimes and whether it is appropriate to apply the application of proof of elements of abuse of authority Article 3 of the PTPK Law in the decision of case Number 74 / Pid.Sus-TPK / 2021 / PN.Bdg. From the results of the research, it was found that the PTPK Law adheres to a formal unlawful nature where Article 2 paragraph (1) of the PTPK Law is the genus while Article 3 is the species. However, there are no clear indicators of differentiation between the two articles so that the practice of application varies. The application of abuse of authority in a quo case is not appropriate because the Defendant's actions were committed in his capacity as an official in the private sector. In addition, the value of state financial losses above Rp.250,000,000 (two hundred and fifty million rupiah) makes Article 2 paragraph (1) of the PTPK Law more feasible to apply.